2021
DOI: 10.1101/2021.04.19.21255739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal analysis shows durable and broad immune memory after SARS-CoV-2 infection with persisting antibody responses and memory B and T cells

Abstract: SUMMARYEnding the COVID-19 pandemic will require long-lived immunity to SARS-CoV-2. We evaluated 254 COVID-19 patients longitudinally from early infection and for eight months thereafter and found a predominant broad-based immune memory response. SARS-CoV-2 spike binding and neutralizing antibodies exhibited a bi-phasic decay with an extended half-life of >200 days suggesting the generation of longer-lived plasma cells. In addition, there was a sustained IgG+ memory B cell response, which bodes well for a r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
135
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(156 citation statements)
references
References 50 publications
18
135
2
Order By: Relevance
“…Levels of IgA and IgG antibodies at the 6-month follow-up were approximately half that of their assumed maximum value measured 6 weeks after disease onset [23], and remained stable up to the 12-months follow-up, thereby showing a biphasic decrease as previously described [24,25]. In contrast to IgM antibodies, IgG antibodies specifically directed against the spike protein of SARS-CoV-2 persist relatively stable over time as described by Dan JM et al, who found a percentage of 90% spike IgG-positive convalescents half a year after COVID-19 [26].…”
Section: Discussionsupporting
confidence: 75%
“…Levels of IgA and IgG antibodies at the 6-month follow-up were approximately half that of their assumed maximum value measured 6 weeks after disease onset [23], and remained stable up to the 12-months follow-up, thereby showing a biphasic decrease as previously described [24,25]. In contrast to IgM antibodies, IgG antibodies specifically directed against the spike protein of SARS-CoV-2 persist relatively stable over time as described by Dan JM et al, who found a percentage of 90% spike IgG-positive convalescents half a year after COVID-19 [26].…”
Section: Discussionsupporting
confidence: 75%
“…Although the difference between both groups continuously disappeared until 3 weeks after 2 nd vaccination, anti-spike antibody titers were still 2-4 times higher and neutralization capacities against the unmutated virus was almost twice as strong in COVID-19convalescent compared with COVID-19-negative individuals. Importantly, the interval between SARS-CoV-2 infection and vaccination did not affect the extent of the described responses, confirming that immune memory did not significantly decrease within the observed temporal range of up to one year between SARS-COV-2 infection and vaccination (26).…”
Section: Discussionsupporting
confidence: 55%
“…Similar findings have been reported in healthcare workers, where older age (in those of working age) was associated with higher maximum anti-nucleocapsid IgG levels and longer half-lives 15 . Others have also reported associations between older age and higher immune responses, including IgG and memory B cells 37 . One postulated mechanism is that older adults exhibit higher IgG levels because they expand their catalogue of memory B and T cells through accumulated memory 38 .…”
Section: Discussionmentioning
confidence: 97%